2016
DOI: 10.1111/bjd.14600
|View full text |Cite
|
Sign up to set email alerts
|

Influence of meteorological data on sun tolerance in patients with erythropoietic protoporphyria in France

Abstract: This study proposes a benefit of natural progressive sun exposure for patients with EPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…We need to follow-up the PP level of incomplete EPP carefully in the future. A previous report found that 40% of EPP patients showed an improvement in their symptoms, following a build-up of sunlight tolerance after repeated exposure (42). EPP patients seem to benefit from UV 'desensitization' therapy, and anecdotal evidence suggests that natural sunlight exposure improves light tolerance (43).…”
Section: Clinical Features and Course In Japanese Erythropoietic Protmentioning
confidence: 98%
See 1 more Smart Citation
“…We need to follow-up the PP level of incomplete EPP carefully in the future. A previous report found that 40% of EPP patients showed an improvement in their symptoms, following a build-up of sunlight tolerance after repeated exposure (42). EPP patients seem to benefit from UV 'desensitization' therapy, and anecdotal evidence suggests that natural sunlight exposure improves light tolerance (43).…”
Section: Clinical Features and Course In Japanese Erythropoietic Protmentioning
confidence: 98%
“…Afamelanotide, a potent α-melanocyte-stimulating hormone (α-MSH) analogue, was approved for treatment of EPP by the European Medicines Agency in 2014. Afamelanotide can darken the skin colour and increase tolerance to sunlight exposure without pain (42,43). Afamelanotideinduced eumelanin synthesis provided photoprotection and decreased the consequences of phototoxicity (46).…”
Section: Clinical Features and Course In Japanese Erythropoietic Protmentioning
confidence: 99%
“…It is extremely challenging to investigate the efficacy of a potentially beneficial treatment in EPP because, as Corbett et al stated in 1977, it is difficult to assess the efficacy of treatment in a disease where signs and symptoms are provoked by sunlight. Light exposure is unpredictable in many climates [17] and symptoms can be prevented by avoiding light. Moreover, results of artificial irradiation tests are unreliable, because the intolerance of individual patients to light varies from one occasion to another, even in the absence of treatment, and some patients show consistently negative tests when artificial light is used [18].…”
Section: Overview Of Treatment Optionsmentioning
confidence: 99%
“…Also, study is difficult, particularly because people with EPP become frightened of sunlight exposure, so in the randomised studies (Europe and the USA) patients may still have gone out less than they would have been able to for fear of painful reactions, so this study endpoint might not have fully reflected the benefits of afamelanotide. Conversely, perhaps many of those who received afamelanotide guessed they were on active treatment because of tanning and so went out longer (so possibly gaining benefit through greater exposure to sunlight 38 ).…”
Section: Acute Phototoxic Symptomsmentioning
confidence: 99%